Are bored minds more likely to be addicted? The relationship between boredom proneness and problematic mobile phone use. (September 2020) - Yang, Xiu-Juan; Liu, Qing-Qi; Lian, Shuai-Lei; Zhou, Zong-Kui
Highlights: Boredom proneness was a salient vulnerability factor for problematic mobile phone use. Depression acted as an important mediator. Attentional control acted as a complex moderator. Abstract: Background: Boredom proneness has been demonstrated as a salient vulnerability factor for problematic mobile phone use. However, the mediating and moderating mechanisms underlying this relationship are less investigated. In the current study, we constructed an integrative moderated mediation model to test the mediating role of depression and the moderating role of attentional control in the relationship between boredom proneness and problematic mobile phone use. Method: A total of 1099 college students ( M age  = 20.04; SD  = 1.25) were recruited to fill out the questionnaires measuring boredom proneness, depression, problematic mobile phone use, and attentional control. Results: Depression partially mediated the relationship between boredom proneness and problematic mobile phone use. Attentional control moderated the indirect relationship between boredom proneness and problematic mobile phone use through depression, with the indirect relationship being weaker for college students with higher levels of attentional control. Moreover, attentional control moderated the direct relationship between boredom proneness and problematic mobile phone use, in that this relationship was stronger for college students with higher levels of attentional control. Conclusions: These findings illuminate the pathway through which boredom proneness is linked to problematic mobile phone use (i.e., mediation) and the condition on which the relationship between boredom proneness and problematic mobile phone use depends (i.e., moderation). More importantly, this study revealed the potential "double-edged sword" effect of attentional control. These findings have implications for early intervention and prevention of problematic mobile phone use in college students.